UMKM Go Online Upaya Lawan Covid-19 Kelompok Ibu-ibu PKK Kelurahan Lubang Buaya Jakarta Timur - Kartika Yuliantari; Suparman Hilawu; Riris Lestiowati; Mohammad Amas Lahat (Jurnal Abdimas Ekonomi dan Bisnis, 2021)
Since the Corona Virus pandemic has disrupted almost all business industries from various sectors, and changed the behavior of the world community in all circles. Likewise, the impact of Covid-19 was most pronounced in the Micro, Small and Medium Enterprises (MSMEs) sector which experienced problems with the low ability of MSME players to use technology TO market products, a decrease in sales turnover results, and problems in hampered distribution of goods. The solutions offered in this PM activity to solve the problems faced are prioritized in terms of increasing the sales ability of PKK Jamaah Masjid Ar-Royyan women as MSME business actors by going online, so that it is expected to increase sales turnover results and smoothen the distribution of goods. With the implementation of PM through training provided through zoom, it is hoped that the PKK women of Lubang Buaya Village, East Jakarta as MSME business actors can improve their ability to market their products online in the midst of the Covid-19 pandemic so that their businesses can survive and get more advanced. Output targets in the form of articles in print or electronic mass media, activity videos, and increased knowledge of online marketing (go online). The method of implementation in this activity consists of the preparation stage, namely by conducting a survey at the location where community service activities will be carried out, the implementation stage, namely marketing training through go online in an effort to increase sales and distribution of goods as well as the monitoring and evaluation stage to find out how much increased ability you have. by partners